Performance of four scoring systems in predicting the need for massive transfusion in Iranian trauma patients - Negin Pouroushaninia; Zahra Ramezani; Atefeh Jahangiri; Niyousha Rahimimovaghar; Gerard O'Reilly; Vali Baigi; Vafa Rahimi-Movaghar (PLoS ONE, 2026)
Background Post-traumatic hemorrhage is a leading cause of death if not promptly identified and treated. This study aimed to compare the performance of four scoring systems in predicting the need for massive transfusion (MT) in trauma patients. Methods This retrospective cohort study analyzed data from trauma patients admitted to Sina Hospital in Tehran between July 2021 and December 2024. All trauma patients who received at least one unit of packed red blood cells were included in the study. Patients were evaluated for the need for MT, and four scoring systems were compared between those who did and did not receive MT. The discriminative ability of the Shock Index (SI), Assessment of Blood Consumption (ABC), Revised Assessment of Bleeding and Transfusion (RABT), and Trauma-Associated Severe Hemorrhage (TASH) was evaluated using the concordance index (C-index) and logistic regression models. Results A total of 329 trauma patients were included, with a mean age of 49.2 (SD = 20.8) years; 244 (74.2%) were male. MT occurred in 36 patients (10.9%). All four scoring systems were significantly associated with the need for MT (p < 0.001) and showed comparable discriminative performance (C-index range: 0.81–0.84). At predefined cutoff values, sensitivity ranged from 63.9% to 94.4%, specificity from 60.0% to 94.2%, PPV from 22.4% to 59.5%, and NPV from 95.5% to 98.9%. In univariable logistic regression, an ABC score ≥ 2 was significantly associated with MT (OR: 36.9; 95% CI: 15.6–87.3), followed by an RABT score ≥ 2 (OR: 25.5, 95% CI: 11.2–58.1) and a TASH score ≥ 6 (OR: 25.2, 95% CI: 5.9–106.9). Conclusion All four scoring systems showed significant associations with the need for MT. These tools may assist clinicians in the early risk stratification of trauma patients; however, given the moderate positive predictive values in this low-prevalence setting, they should be used as adjuncts to clinical judgment rather than as standalone triggers for massive transfusion activation.